Postura intelectual e ambiguidade em Florestan Fernandes - Proto, Leonardo Venicius Parreira (2017)
In this doctoral dissertation, we research the intellectual stance of Florestan Fernandes and we also seek to flesh out the reasoning that generated such a position and why he assumes this stance in the national and intellectual scenario. His intellectual perspective approximated the political standings influenced by Leninism and Gramscianism, according to his choice of militancy through the institutionalized political path, in his performance in the political party and his involvement with parliamentary activity. The party's choice as an instrument of insertion in national public life was associated with his conception of Marxism and the defense of what is called proletarian socialism. In methodological terms, we analyzed his bibliography which has connections with Marxism, the Workers' Party (PT), Socialism, class struggles and bourgeois democracy, as well as published interviews, printed and on videos, in order to verify his thoughts on these issues. In this regard, as it can be verified in this work, we rely on the theoretical framework of Marxism to analyze his intellectual production according to his social class and sense of belonging, in this case the intellectuality, and from the notion of social sphere and the intellectual sphere. We discuss his standing and stance in the face of Brazilian reality and what he considered as Marxism and the forms of working class action in favor of the constitution of proletarian socialism. For us, there is an approximation of the ideological contributions of Leninism-Gramscianism in his conception of Marxism, which we conceive as the deformation of Marxism in terms of the false systematized consciousness of reality, by defending, in his stances, institutionalized organizations such as the party and the trade union, understood by him as instruments of struggle necessary for the working class to overcome capitalism and extinguish bourgeois domination. His intellectual perspective is determined by his Leninist and Gramscian political formation which allows him to act in bureaucratic organizations expressing, thus, a political positioning derived from his connections with the university and the political party. Therefore, the need of getting himself involved with the burning issues of national debate and the class struggles made him defend institutionalized instruments of struggle, generating an ambiguous outlook assumed throughout the development of his trajectory of action in the scope of the university and of the political party, which confirms his distancing from authentic Marxism and its revolutionary character.